BER Performance Evaluation of 4D-8PSK-TCM Decoder - Kim, Song; Kim, Jae Hyun (ICTC 2019 - 10th International Conference on ICT Convergence: ICT Convergence Leading the Autonomous Future, 2019)
Satellite-based services, including 5G communications, require efficient high-speed communication technology. The Consultative Committee for Space Data System (CCSDS)recommends the 4 Dimension 8-ary Phase Shift Keying Trellis Coded Modulation (4D-8PSK-TCM) system to transmit large amounts of data at high speeds using X-Band, which is often used by Low Earth Orbit (LEO) satellites. In this paper, we explain the 4D-8PSK-TCM decoder with transmission efficiency of 2.0 bits/channel-symbol and build simulation model using MATLAB. The performance is evaluated in terms of the Bit Error Rate(BER) according to trace-back depth of the Viterbi decoder. We validate that the simulation model does not differ in BER performance from that of CCSDS. Also, we confirmed that the deeper trace-back depth of the Viterbi Decoder, the worse BER performance.
Keywords: 4D-8PSK-TCM; Consultative committee for space data systems; High-speed communications; LEO satellite communications; Low earth orbit satellites; Satellite-based services; Transmission efficiency; Trellis coded modulation; 4D-8PSK-TCM; LEO satellite communication; Viterbi algorithm